2021
DOI: 10.17221/137/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic bio-fortification of iron, zinc and selenium enhance growth, quality and uptake of different sorghum accessions

Abstract: Agronomic bio-fortification is one of the main approaches for mitigation of micronutrient shortage in human populations and endorses sustainable production of food and feed. Studies related to agronomic bio-fortification of crops are mainly focused on single or rarely two micronutrients application, and no attempt has made to study the combined effect of zinc (Zn), iron (Fe) and selenium (Se) on forage sorghum. Therefore, this research was accomplished to evaluate the effect of Zn, Fe and Se bio-fortification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In this study, the decrease in Ca 2+ contents of shoot under salinity and combined treatments of NaCl in Faba bean might be attributable to the reduction in Ca 2+ availability and a limitation of Ca 2+ absorption and transport to growth tissue under salinity [62]. Zinc plays a significant role in chlorophyll synthesis, pollen function, and fertilization and stabilizes proteins, membranes, and DNA-binding proteins such as Zn fingers [63]. Moreover, the foliar application of ZnONPs treatments considerably enhanced the nutritional content of Sweet Basil Plant leaves, including N, P, K, Fe, Zn, and Cu, compared to control leaves [64].…”
Section: Discussionmentioning
confidence: 79%
“…In this study, the decrease in Ca 2+ contents of shoot under salinity and combined treatments of NaCl in Faba bean might be attributable to the reduction in Ca 2+ availability and a limitation of Ca 2+ absorption and transport to growth tissue under salinity [62]. Zinc plays a significant role in chlorophyll synthesis, pollen function, and fertilization and stabilizes proteins, membranes, and DNA-binding proteins such as Zn fingers [63]. Moreover, the foliar application of ZnONPs treatments considerably enhanced the nutritional content of Sweet Basil Plant leaves, including N, P, K, Fe, Zn, and Cu, compared to control leaves [64].…”
Section: Discussionmentioning
confidence: 79%
“…[29] mentioned that silicon has a role in improving plant growth indicators, including leaf area, by reducing the influence of biotic and abiotic stress on the plant. Also, micronutrients could have a role in influencing the leaf area of the plant, as indicated by [30] that fertilizing with iron and zinc has a significant effect in increasing the leaf area of the sorghum plant. [31] indicated that fertilizing with zinc and boron led to an increase in the leaf area of the sorghum plant.…”
Section: Leaf Area (M 2 )mentioning
confidence: 99%
“…While the treatment of the sorghum variety has significantly affected the leaf area of the plant, the variety (C 2 ), which achieved a leaf area of 0.45 M 2 , outperformed the variety (C 1 ), which achieved a leaf area of 0.34 M 2 , and this may be due to the difference between the two varieties in their genetic characteristics [14]. The results of Table (3) also indicate that the interaction between leaching requirements and the fertilization treatment has significantly affected the leaf area of the plant, with the highest average of the leaf area being 0.50 m 2 for the interaction treatment (L 1 F 5 ) and the lowest average was 0.27 m 2 for the treatment (L 1 F 0 ), which may be due to the role of leaching requirements in reducing soil salinity [24], in addition to the impact of fertilization treatments, whether in improving soil properties, increasing plant resistance to Environmental stresses, or improving plant growth indicators [31,22,30,21,29]. The results of Table (3) also indicate that the interaction between the sorghum variety and the leaching requirements, and the interaction between the sorghum variety and fertilization treatment, and the triple interaction between the treatment of sorghum variety, leaching requirements, and fertilization treatment, did not have a significant effect on leaf area of the plant.…”
Section: Leaf Area (M 2 )mentioning
confidence: 99%
“…A number of studies have shown the utility of agronomic biofortification with zinc for plant growth and development (Haslett et al, 2001, Sharma et al, 2013, Oliveira et al, 2020, productivity (Qureshi et al, 2021) and grain quality (Rashid, 1992;Dhaliwal et al, 2009). Zinc deficiency causes chlorosis in the leaves of plants.…”
Section: Introductionmentioning
confidence: 99%